2021
DOI: 10.26603/001c.21250
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Hamstring Tendinopathy: A Systematic Review of Interventions

Abstract: Background Proximal hamstring tendinopathy affects athletic and non-athletic populations and is associated with longstanding buttock pain. The condition is common in track and field, long distance running and field-based sports. Management options need to be evaluated to direct appropriate clinical management. Purpose/Hypothesis To evaluate surgical and non-surgical interventions used in managing proximal hamstring tendinopathy. Study design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…generalisation of findings), (iv) imprecision (total participants <300 for each outcome; wide CI) and (v) other considerations (e.g. publication bias, large loss to follow‐up) (Nasser et al., 2021; Schünemann et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…generalisation of findings), (iv) imprecision (total participants <300 for each outcome; wide CI) and (v) other considerations (e.g. publication bias, large loss to follow‐up) (Nasser et al., 2021; Schünemann et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasound-guided fenestration and PRP injection can be used for treating patients with hamstring tendinopathy. Previous studies have shown pain relief and functional improvement in the short-to-mid-term, while others have reported no relevant clinical effectiveness ( 10 , 25 ) . At any rate, the procedure can be considered when other non-invasive treatments have failed, given that its safety is well-established.…”
Section: Hamstringsmentioning
confidence: 99%
“…Various interventions for PHT have been explored in the literature, including exercise-based rehabilitation, SWT, injectables such as PRP and CSI, and surgery [ 82 ]. Unfortunately, the quality of evidence supporting any intervention is, at best low, with most studies limited to case series without control groups [ 82 ].…”
Section: Management Of Proximal Hamstring Tendinopathymentioning
confidence: 99%